Digital Health Literacy and Healthcare Utilization Behavior Among JKN Participants in Gowa Regency: A Preliminary Descriptive Study - Astari Pratiwi Nuhrintama; Rezky Putri Indarwati Abdullah; Hedi Alfian; Ashari Fachrizal Nuhrintama; Nurul Mukhlisa (Global Health Practice Journal, 2026)
Background: Low Digital Health Literacy (DHL) and health misinformation on social media are believed to contribute to irrational primary healthcare utilization among Jaminan Kesehatan Nasional (JKN) participants, yet empirical evidence from South Sulawesi remains limited.Aims: To describe DHL levels, digital health information consumption patterns, and potentially risky healthcare utilization behaviors among JKN participants in Gowa Regency.Methods: A descriptive cross-sectional study was conducted in October–November 2024 at Klinik Nuhrintama, Gowa. Twenty-five active JKN participants were recruited via consecutive sampling. Data were collected using a structured questionnaire measuring DHL (adapted DHLI, 7 items), digital information consumption patterns, and healthcare utilization behaviors, and analyzed descriptively.Results: Over half of respondents (52.0%) demonstrated moderate-to-low DHL (mean 20.8, SD=5.6), with the lowest scores in source reliability assessment (2.72) and verifying before acting (2.60). Most participants (80.0%) consulted social media prior to seeking care, predominantly via Google (44.0%) and TikTok (28.0%). Only 12.0% consistently verified information with a healthcare professional. Potentially risky behaviors were reported by 36.0% of respondents, most commonly requesting medications or supplements based on social media content (32.0%).Conclusion: A critical gap exists between digital access and health literacy in Gowa Regency, underscoring the need for larger-scale studies with validated instruments and robust analytic designs.